Jean-Pierre and Luc Dardenne - Mai, Joseph (Book collections on Project MUSE., 2010)
For over a decade, Jean-Pierre and Luc Dardenne have produced highly original and ethically charged films that immerse their audiences in an intense and embodied viewing experience. This study of the Belgian brothers delivers sophisticated close analyses of their directorial style and explores the many philosophical issues dealt with in their films (especially the ethics of Emmanuel Levinas). It discusses the Dardennes' varied and searching career from its inception in the late 1970s, starting with the working-class political consciousness and lost utopias of their documentary period; passing through their transition toward fictional narrative, experimental techniques, and familial themes; and finishing with a series of interpretations of the brothers' recent work. In such highly influential films such as La promesse, Rosetta, The Son, and The Child, the brothers have recast filmmaking through what the author calls a "sensuous realism"--Realism capable of touching the audience with the most compelling problems and moral dilemmas of contemporary society. This volume also features an interview in which the Dardennes discuss their approach to film production and the direction of actors.